Association between neutrophil to lymphocyte ratio and pulmonary arterial hypertension - Abdulkadir Yıldız; Hasan Kaya; Faruk Ertas; Mustafa Oylumlu; Mehmet Zihni Bilik; Murat Yüksel; Nihat Polat; Mehmet Ata Akil; Zuhal Atılgan; Mehmet Sıddık Ülgen (KARE Publishing, 2013)
Objectives: Pulmonary hypertension (PH) is composed of a heterogeneous group of disorders marked by increased pulmonary artery resistance leading to right heart failure, with high mortality. Evidence is increasing to propose that inflammation plays a significant role in the pathophysiological mechanism. Increased prevalence of PH in patients with systemic inflammatory diseases is already known. Herein, we sought to evaluate the association between neutrophil to lymphocyte ratio (N/L ratio) and pulmonary arterial hypertension (PAH). Study design: Twenty-five patients with PAH and 25 controls were evaluated. Baseline clinical and echocardiographic variables were obtained. Complete blood counts in all patients and controls were reviewed retrospectively. Results: The N/L ratio was higher in patients with PAH compared to healthy volunteers (p=0.05). A cut-off value of 1.65 for N/L ratio predicted the presence of PAH with 72% sensitivity and 69% specificity. After multivariate analysis, only N/L ratio remained a significant predictor of PAH. Conclusion: We showed for the first time that N/L ratio was significantly increased in patients with PAH compared to controls.